Undergraduate Nurse Student’s Perceptions of Being Health Volunteer during Merapi Mountain Eruption 2010 - Erna Rochmawati (Universitas Muhammadiyah Yogyakarta, 2011)
This current study aimed to investigate undergraduate nurse students’ perceptions and experiences of being health volunteer during Mount Merapi eruption on 2010. A nonexperimental, descriptive design was used. A total sampling of 26 undergraduate nurse students who become health volunteers during Mount. Merapi eruption completed self administered questionnaire. The questionnaire which consisted open and closed ended questions was used to measure students’ self awareness and what they have learnt. Data were aggregated and analyzed using simple descriptive analysis. Result indicated that undergraduate nurse students had internal motivation of being health volunteers during disaster. This study found results of students’ self assessment of their knowledge and skills capability. Findings of this study contributes benefits, future impact of being health volunteers. Students’ perceptions and experiences during disaster underscores the importance factors in the promotion of disaster management competency in nursing education.